2008
DOI: 10.1002/dneu.20667
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic embryonic sensory stimulation alters multimodal behavior and cellular activation

Abstract: Embryonic vision is generated and maintained by spontaneous neuronal activation patterns, yet extrinsic stimulation also sculpts sensory development. Because the sensory and motor systems are interconnected in embryogenesis, how extrinsic sensory activation guides multimodal differentiation is an important topic. Further, it is unknown whether extrinsic stimulation experienced near sensory sensitivity onset contributes to persistent brain changes, ultimately affecting postnatal behavior. To determine the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Potential efficacy of prenatal neurobehavioral therapy is supported by growing evidence from non-human animals and from humans that learning occurs prior to birth. Markham and colleagues have demonstrated that birds learn about the calls of conspecifics while still in the egg, and that this embryonic programming alters neural cellular activation after birth and also characteristics of later vocalizations69. A landmark study by Partanen and colleagues presented evidence of experienced-based neuroplasticity in human fetuses .…”
Section: Discussionmentioning
confidence: 99%
“…Potential efficacy of prenatal neurobehavioral therapy is supported by growing evidence from non-human animals and from humans that learning occurs prior to birth. Markham and colleagues have demonstrated that birds learn about the calls of conspecifics while still in the egg, and that this embryonic programming alters neural cellular activation after birth and also characteristics of later vocalizations69. A landmark study by Partanen and colleagues presented evidence of experienced-based neuroplasticity in human fetuses .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Markham, Shimizu, and Lickliter [79] presented augmented amounts of auditory stimulation to bobwhite quail embryos during early, middle, or late prenatal development and then tested postnatal responsiveness to species typical auditory and visual cues. Embyos receiving auditory stimulation during middle or late stages of prenatal development showed altered postnatal visual responsiveness when compared to controls.…”
Section: Changes In Sensory Organization Associated With Changes In Smentioning
confidence: 99%
“…The loss of early auditory experience perturbs normal perceptual maturation in young animals, including children (Gottlieb, 1975; Kerr et al, 1979; Halliday and Bishop, 2005; Kidd et al, 2002; Clements and Kelly, 1978; Knudsen et al, 1984; Kelly et al, 1987; Moore et al, 1999; Parsons et al, 1999). Similarly, chronic exposure to sound during development can disrupt normal perceptual sensitivity (Gottlieb, 1991; Han et al, 2007; Zhang et al, 2008; Markham et al, 2008). These findings are consistent with an even larger literature showing that neural coding, which often serves as a proxy for behavior, can be impacted by similar manipulations (for reviews, see Keuroghlian and Knudsen, 2007; Sanes and Bao, 2009)…”
Section: Introductionmentioning
confidence: 99%